The Crucial Roles of Phospholipids in Aging and Lifespan Regulation - Dai, Yucan; Tang, Haiqing; Pang, Shanshan (Frontiers in Physiology, 2021)
Phospholipids are major membrane lipids that consist lipid bilayer. This basic cellular structure acts as a barrier to protect the cell against various environmental insults and more importantly, enables multiple cellular processes to occur in subcellular compartments. Numerous studies have linked the complexity of membrane lipids to signal transductions, organelle functions, as well as physiological processes and human diseases. Recently, crucial roles for membrane lipids in the aging process are beginning to emerge. Here, we summarize current advances in our understanding of the relationship between membrane lipids and aging with emphasis on phospholipid species. We survey how major phospholipid species change with age in different organisms and tissues, and some common patterns of membrane lipid change during aging are proposed. Further, the functions of different phospholipid molecules in regulating healthspan and lifespan, and their potential mechanisms of action are also discussed.